TEACHING A SECOND LANGUAGE THROUGH INTERACTIVE METHODS: ENHANCING LEARNERS’ COMMUNICATIVE COMPETENCE IN SECONDARY SCHOOL CLASSROOMS - Turdiyeva Rano Khusniddin kizi (International Journal of Literature and Language Studies, 2026)
The effectiveness of second language instruction largely depends on learners’ engagement and opportunities for meaningful communication. This study investigates the impact of interactive teaching methods on second language learning among secondary school students aged 12–17. A mixed-methods approach was employed involving 60 students who participated in a six-week instructional program based on role plays, group discussions, educational games, collaborative tasks, and peer-learning activities. Data were collected through classroom observations, speaking assessments, questionnaires, and learner feedback. The findings indicate that interactive teaching methods positively influence students’ communicative competence, motivation, classroom participation, and speaking confidence. The study concludes that integrating interactive activities into language instruction creates a learner-centered environment that facilitates effective language acquisition and meaningful communication.